(untitled) (Global Business Management Review (GBMR), 2019)
This paper examines the causes of food waste in the grocery retail sector and develops a framework for how logistics and supply chain management actions could mitigate this problem. Customer preferences and perceptions for food are analyzed to determine their influence on the structure of food supply chains and their indirect contribution to food waste at grocery store levels. Based on the literature review, our study identifies five main categories that influence food waste: information flow, demand uncertainties and forecast, inefficiencies in the safety stock and inventory management, disruptions of the cold supply chain, and customers’ perceptions and preferences for food in stores. We propose solutions to these causes as a possible way to alleviate and minimize food waste in the grocery retail sector. At a managerial level, the findings of this paper can lead to positive changes by creating a more efficient food supply chain structure that minimizes food waste in the grocery retail sector. Additionally, the results can have individual implications at a social level regarding customer preferences for and perceptions of food at grocery stores.